Advertising theory - Rodgers, Shelly; Thorson, Esther (Routledge communication series, 2019)
Advertising Theory provides detailed and current explorations of key theories in the advertising discipline. The volume gives a working knowledge of the primary theoretical approaches of advertising, offering a comprehensive synthesis of the vast literature in the area. Editors Shelly Rodgers and Esther Thorson have developed this volume as a forum in which to compare, contrast, and evaluate advertising theories in a comprehensive and structured presentation. With new chapters on forms of advertising, theories, andconcepts, and an emphasis on the role of new technology, this new edition is uniquely positioned to provide detailed overviews of advertising theory. Utilizing McGuire's persuasion matrix as the structural model for each chapter, the text offers a wider lens through which to view the phenomenon of advertising as it operates within various environments. Within each area of advertising theory--and across advertising contexts--both traditional and non-traditional approaches are addressed, including electronic word-of-mouth advertising, user-generated advertising, and social media advertising contexts. This new edition includes a balance of theory and practice that will help provide a working knowledge of the primary theoretical approaches and will help readers synthesize the vast literature on advertising with the in-depth understanding of practical case studies and examples within every chapter. It also looks at mobile advertising in a broader context beyond the classroom and explores new areas such as native advertising, political advertising, mobile advertising, and digital video gaming.